2021
DOI: 10.3390/ijgi10030116
|View full text |Cite
|
Sign up to set email alerts
|

Twitter Use in Hurricane Isaac and Its Implications for Disaster Resilience

Abstract: Disaster resilience is the capacity of a community to “bounce back” from disastrous events. Most studies rely on traditional data such as census data to study community resilience. With increasing use of social media, new data sources such as Twitter could be utilized to monitor human response during different phases of disasters to better understand resilience. An important research question is: Does Twitter use correlate with disaster resilience? Specifically, will communities with more disaster-related Twit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 44 publications
0
11
0
1
Order By: Relevance
“…Many theoretical studies on urban resilience to disasters have been completed [41,54,55] and existing studies show that the urban recovery time after a natural hazard is associated with socioeconomic disparities [26,33,56]. In this study, we further explored the urban resilience from the NLR anomalies by examining the response and recovery time during Hato.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many theoretical studies on urban resilience to disasters have been completed [41,54,55] and existing studies show that the urban recovery time after a natural hazard is associated with socioeconomic disparities [26,33,56]. In this study, we further explored the urban resilience from the NLR anomalies by examining the response and recovery time during Hato.…”
Section: Discussionmentioning
confidence: 99%
“…The recovery stage refers to the process over which human activities gradually bounce back normal and it is widely used to study a city's resilience [26,33,54]. In this study, we calculated the recovery time to evaluate how fast a city returns to normal after the typhoon.…”
Section: Response To Typhoon and Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Significant associations between social media use and socioeconomic factors, households in rural areas, lower-income groups, and racial minorities are more likely to report greater inaccuracies in social media information [39]. Significant positive correlations are found between Twitter use density and resilience indicators, confirming that communities with higher resilience capacity or those characterized by better social-environmental conditions tend to have higher Twitter use [40].…”
Section: Disparities In Social Mediamentioning
confidence: 91%
“…Niles et al (2019) reported that use of Twitter varies by the various stages of disaster and by the type of disaster, with use in hurricane events peaking at the preparation stage and in flood and tornado events at the "during" or recovery stage. Wang et al (2021) found that Twitter use has a positive correlation with hurricane resiliency, suggesting that it can be a tool to enhance resilience. Machine learning techniques have revealed the temporal evolution of the various "stages" of Tweet applications in the context of a single disaster (Arapostathis, 2021), with other research calling for further integration of machine-learning-derived information in this regard (Dwarakanath et al, 2021).…”
Section: Social Media Effectivenessmentioning
confidence: 98%